The IEE electrician's guide to the building regulations covering approved document P : electrical safety in dwellings and including guidance on the Scottish building regulations. (Institution of Engineering and Technology, 2008)
The Electrician's Guide to the Building Regulations will ensure domestic installers not only comply with Part P, but also with other Building Regulations, including Fire Safety, Ventilation and Conservation of Energy. The second edition of this title has been updated to cover the 17th edition of the IEE Wiring Regulations (BS 7671). It also includes a new chapter on requirements for Scotland. In addition, references to British Standards have been updated. The book is spiral bound making it practical to use. It is supported throughout by full colour illustrations, simple standardised circuits and a comprehensive index.